SUPERVISION STRATEGY OF MADRASAH HEADS IN DEVELOPING TEACHER PERSONALITY COMPETENCIES: A LITERATURE REVIEW OF ISLAMIC EDUCATION MANAGEMENT - Muhammad Aris Kurniawan; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This article aims to analyze the supervision strategies employed by madrasah principals in developing teachers’ personality competence through a comprehensive review of relevant literature. The study adopts a qualitative approach using a literature review design and content analysis of educational regulations, scholarly books, peer-reviewed journal articles, and related theses. The analysis reveals that effective principal supervision is implemented as a continuous developmental cycle consisting of needs assessment, systematic classroom observation, reflective professional dialogue, indicator-based evaluation, and sustainable follow-up actions. This supervision model not only improves teachers’ professional performance but also strengthens the five essential dimensions of personality competence: personal stability, emotional maturity, wisdom in decision-making, professional authority, and noble character that serves as a model for students and the school community. Furthermore, the findings indicate that successful supervision requires supportive leadership, constructive communication, and ongoing mentoring to foster teachers’ personal and professional growth. This article concludes that principal supervision should be positioned not merely as an administrative function but as an integrated managerial and moral strategy for systematically developing teachers’ personality competence and improving the overall quality of education in madrasahs.